Upaya Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik dengan menggunakan Model Pembelajaran Contextual Teaching and Learning - Yosua Kristian Firmanyo Lase; Toroziduhu Waruwu; Novelin Andriani Zega; Hardikupatu Gulo (Journal on Education, 2024)
Learning outcomes and student activity can be improved through contextual teaching and learning models. This research aims to reveal increased activity and learning outcomes with this model using classroom action methods: planning, action, observation and reflection. The data collection instruments were observation sheets, learning outcomes tests, photo documentation, and data analyzed descriptively. The research population was class VIII students, the sample was drawn by purposive sampling as many as 19 people, and the research location was SMP Negeri 2 Hiliduho. The research results concluded that: this learning process can increase activity and learning outcomes; in cycle I the average increase was 58.33% and cycle II 83.86%. Learning activity also increased, in cycle I 63.71% and in cycle II 87.83%. Learning outcomes increased to good, in cycle I it rose to 67.05, classified as sufficient with a completion percentage of 57.89% and in cycle II, the average learning outcome was 82.84, classified as good with a completion percentage of 89.47%. It is recommended for teachers to use this model.